Semi-analytical sensitivity analysis procedure for frictional contact problems - Chen, Xian; Hisada, Toshiaki; Nakamura, Kazuhiro; Mori, Masahiko (Computer Assisted Methods in Engineering and Science, 2023)
Although there is a need for sensitivity analysis for frictional contact problems in many engineering fields, research work on it has rarely been reported due to the complexity of the problems. In this paper, a sensitivity analysis procedure based on a semi-analytical method for frictional contact problems is presented. The unbalance force due to the variation of design parameters is evaluated numerically, thus the related routine of an existing FEM code can be utilized regardless of the friction law employed. The continuum-mechanics-based formulation is carried out first and then a discretized form is derived. The stick state is modeled by introducing a penalty-type constraint. A couple of numerical examples, including a realistic leaf spring structure used in nuclear power plants, are given to demonstrate the effectiveness of the proposed approach.